Identidades em performance: abuelas em fronteiras - Penha, Bruna (2013)
This paper work brings to discussion the Paraguayan women as a polissemic and ambiguous symbol. Migrant grandmothers, who live in the twin cities of Ponta Porã and Pedro Juan Caballero, are our interlocutor. Those cities constitute the dry frontier between Brazil and Paraguay; they are cosmopolitan and peripheral. There, rurality and urbanity, as well as the localization and the globalization, encounter themselves. The main topics of this work are the gender, age and identitary frontiers which those women cross. Each of the frontiers just mentioned is ambiguous in its constitution and in the way it is acted. They are narrated by the grandmothers and make possible to achieve some comprehension on the way those women perform their identities. They also make explicit some of the many social, cultural and political spheres in the personal and transnational relationship in that transfrontier.